ChemInform Abstract: Decarboxylative Halogenation of Indolecarboxylic Acids Using Hypervalent Iodine(III) Reagent and Its Application to the Synthesis of Polybromoindoles. Issue 33 (August 2015) - Hamamoto, Hiromi; Miki, Yasuyoshi; Umemoto, Hideaki; Umemoto, Misako; Ohta, Chiaki; Fujita, Emi; Nakamura, Akira; Maegawa, Tomohiro
Abstract Depending on the N‐protecting group of the substrate, the title reaction generally affords either 1‐(phenylsulfonyl)‐2, 3‐dihaloindoles or 1‐methyl‐3, 3‐dihalooxindoles.